Integration Mania

Calculus Level 4

π 4 π 3 e x ( 2 + sin ( 2 x ) 1 + cos ( 2 x ) ) d x \displaystyle \int_{\frac{\pi}{4}}^{\frac{\pi}{3}} e^x \left ( \frac{2+\sin(2x)}{1 + \cos(2x)} \right) \, dx

If the integral above can be expressed as e π a ( b e π c d ) \large e^{\frac{\pi}{a}} ( be^{\frac{\pi}{c}} - d) , evaluate b 2 c a d 10 \dfrac{ b^2 c}{ad^{10} } .


The answer is 9.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

U Z
Jan 14, 2015

π 4 π 3 e x ( 2 2 c o s 2 x + 2 s i n x c o s 2 c o s 2 x ) \displaystyle \int _{ \dfrac { \pi }{ 4 } }^{ \dfrac { \pi }{ 3 } } e^x(\dfrac{2}{2cos^2x} + \dfrac{2sinxcos}{2cos^2x})

π 4 π 3 e x ( s e c 2 x + t a n x ) \displaystyle \int _{ \dfrac { \pi }{ 4 } }^{ \dfrac { \pi }{ 3 } } e^x(sec^2x + tanx)

e x ( f ( x ) + f ( x ) ) d x = e x f ( x ) + C \displaystyle \int e^x(f(x) + f'(x))dx = e^xf(x) + C

= [ π 4 π 3 e x t a n x ] = \big[_{\frac{ \pi }{ 4 } }^{ \frac { \pi }{ 3 } } e^xtanx \big]

= e π 3 3 e π 4 = e^{\dfrac{\pi}{3}}\sqrt{3} - e^{\dfrac{\pi}{4}}


Note-

e x ( f ( x ) + f ( x ) ) d x = e x f ( x ) + C \displaystyle \int e^x(f(x) + f'(x))dx = e^xf(x) + C

Proof - By parts , take e x e^x as first function

e x f ( x ) d x = e x f ( x ) + C e x f ( x ) d x \displaystyle \int e^x f(x)dx = e^xf(x) + C - \int e^x f'(x)dx

e x ( f ( x ) + f ( x ) ) d x = e x f ( x ) + C \boxed{\displaystyle \int e^x(f(x) + f'(x))dx = e^xf(x) + C}

@Rajdeep Dhingra can't be a level 5 problem , it can be level 2 (if one do'nt know identity , if one know then level 1)

U Z - 6 years, 5 months ago

Log in to reply

Really! I agree! And I was stunned at it being of 280 points.

Kartik Sharma - 6 years, 4 months ago

Haha..really overrated problem

Ayush Garg - 6 years, 3 months ago

One of my hsc textbook problems. Simply overrated .

monty g - 5 years, 11 months ago
Chew-Seong Cheong
Aug 31, 2016

I = π 4 π 3 e x ( 2 + sin ( 2 x ) 1 + cos ( 2 x ) ) d x = π 4 π 3 e x ( 2 + 2 sin x cos x 1 + 2 cos 2 x 1 ) d x = π 4 π 3 e x ( 2 + 2 sin x cos x 2 cos 2 x ) d x = π 4 π 3 e x ( sec 2 x + tan x ) d x = π 4 π 3 e x sec 2 x d x + π 4 π 3 e x tan x d x By integration by parts, = e x tan x π 4 π 3 π 4 π 3 e x tan x d x + π 4 π 3 e x tan x d x f ( x ) = e x , g ( x ) = sec 2 x = e π 3 tan π 3 e π 4 tan π 4 = 3 e π 3 e π 4 = e π 4 ( 3 e π 12 1 ) \begin{aligned} I & = \int_\frac \pi 4 ^\frac \pi 3 e^x \left(\frac {2+\sin(2x)}{1+\cos(2x)} \right) dx \\ & = \int_\frac \pi 4 ^\frac \pi 3 e^x \left(\frac {2+2\sin x \cos x}{1+2 \cos^2 x-1} \right) dx \\ & = \int_\frac \pi 4 ^\frac \pi 3 e^x \left(\frac {2+2\sin x \cos x}{2\cos^2 x} \right) dx \\ & = \int_\frac \pi 4 ^\frac \pi 3 e^x \left(\sec^2 x + \tan x \right) dx \\ & = \color{#3D99F6}{\int_\frac \pi 4 ^\frac \pi 3 e^x \sec^2 x \ dx} + \int_\frac \pi 4 ^\frac \pi 3 e^x \tan x \ dx & \small \color{#3D99F6}{\text{By integration by parts,}} \\ & = \color{#3D99F6}{e^x \tan x \bigg|_\frac \pi 4 ^\frac \pi 3 - \cancel{\int_\frac \pi 4 ^\frac \pi 3 e^x \tan x \ dx}} + \cancel{\int_\frac \pi 4 ^\frac \pi 3 e^x \tan x \ dx} & \small \color{#3D99F6}{f(x) = e^x, \ g'(x) = \sec^2 x} \\ & = e^\frac \pi 3 \tan \frac \pi 3 - e^\frac \pi 4 \tan \frac \pi 4 \\ & = \sqrt 3 e^\frac \pi 3 - e^\frac \pi 4 \\ & = e^\frac \pi 4 \left(\sqrt 3 e^\frac \pi{12} - 1\right) \end{aligned}

b 2 c a d 10 = ( 3 ) 2 12 4 1 10 = 9 \implies \dfrac {b^2c}{ad^{10}} = \dfrac {(\sqrt 3)^2 \cdot 12}{4 \cdot 1^{10}} = \boxed{9}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...